Oppian's Halieutica - Kneebone, Emily (Cambridge University Press, 2022)
Introduction : On fishing – Didactic poetry. Didactic epic – Knowledge and pleasure – Mapping the sea – Morality at sea. Guile – Greed – Lust – Humans and animals. Epic similes – Analogical animals – Humans and other animals – Seas real and unreal. Locating monsters – An empire of fish.
Includes bibliographical references and index
Keywords: Oppian; Halieutica; Didactic poetry; Greek; Fishes in literature; Fishing in literature; Human-animal relationships in literature